COMPARISONAL ANALYSIS OF FLY ASH (CASE STUDY AT PLTU PORT RATU) - Ismail; Ardin Rozandi; Danang Purwanto; Tsulis Iqbal Khairul Amar; Matrunevich Oksana Viktorovna (Nusa Putra University, 2020)
Fly ash can include toxins from high levels of bottom ash in some circumstances, such as burning of solid waste to generate power (resource recovery facilities or waste-to-energy conversion), and combining fly ash and bottom ash together delivers corresponding quantities of contaminants. Under some conditions, fly ash can be classified as non-hazardous waste, but if it is not blended, it can be classified as hazardous waste. The goal of this research was to find out about the differences between fly and bottom ash, as well as the influence of fly ash on bottom ash in terms of avoiding abrasion. In addition, the study's goal was to see how fly ash affected coconut fiber's resistance to abrasion. This study employed a quantitative technique in which the researcher used primary data sources such as questionnaires and observations, as well as secondary data sources such as prior studies. The findings revealed that fly ash had no effect on bottom ash in terms of avoiding abrasion. Furthermore, it is well known that neither fly ash nor bottom ash are effective against coconut fiber. Fly ash has a coarser texture than bottom ash, according to the findings. The regression test revealed that there was no difference between fly ash and bottom ash, as well as coconut coir, in terms of reducing abrasion